1988
DOI: 10.1017/s0003356100019061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of floor area allowance on performance of growing pigs kept on fully slatted floors

Abstract: The experiment compared four different space allowances for growing pigs housed on fully slatted floors. Space allowance {A m 2 ) was defined in relation to live weight (M kg) of the pigs according to the equation A = kM 067 , using values for the constant (it) of 0-024, 0-027, 0-030 and 0-034. Six replicate pens of 12 pigs were housed on each treatment in a controlled environment building. Food was given ad libitum and from 34 kg until slaughter at 85 kg pigs were individually weighed each week and the pen si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 10 publications
2
23
0
2
Order By: Relevance
“…Previous studies (Edwards et al 1988;Gonyou and Stricklin 1998;Spoolder et al 2000) that have eliminated the problem of confounding space and group size (space allowance was maintained constant throughout the trial period by adjusting pen space weekly, based on body weight measurements) and followed allometric calculation of space allowance to treatment groups have indicated the benefit of higher space allowance on daily gain in grower-finishers, as observed in the present study. However, direct comparisons are constrained because of the difference in k values and whether a constant amount of space (based on the k value treatment) was provided throughout the trial in those studies.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Previous studies (Edwards et al 1988;Gonyou and Stricklin 1998;Spoolder et al 2000) that have eliminated the problem of confounding space and group size (space allowance was maintained constant throughout the trial period by adjusting pen space weekly, based on body weight measurements) and followed allometric calculation of space allowance to treatment groups have indicated the benefit of higher space allowance on daily gain in grower-finishers, as observed in the present study. However, direct comparisons are constrained because of the difference in k values and whether a constant amount of space (based on the k value treatment) was provided throughout the trial in those studies.…”
Section: Discussionsupporting
confidence: 64%
“…However, direct comparisons are constrained because of the difference in k values and whether a constant amount of space (based on the k value treatment) was provided throughout the trial in those studies. In a trial with four k values (0.024, 0.027, 0.03 and 0.034), Edwards et al (1988) reported that increasing space allowance increased live weight gain. Although the present results are in agreement with this, they differ from that of Edwards et al (1988) in the range of k values and also in that the space allowances were calculated based on anticipated k value at a market weight of 116 kg, resulting in a gradual reduction in k from the start to the end of the trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the floor-space allowances provided in the present study during the initial period of growth were in excess of what has been considered necessary for maximum growth (Edwards et al 1988;Baxter 1992). Results from previous research evaluating effects of floor-space allowance on growth performance have generally led to the conclusion that daily gain is reduced for pigs penned at space allowances lower than 0.74 m 2 pig -1 during the grow-finish period (Moser et al 1985;NCR-89 1993;McGlone and Newby 1994).…”
Section: Resultsmentioning
confidence: 58%
“…Stocking rate can have a major effect on feed intake as shown by Brumm and Gonyou (2001) who found that a major response to space restrictions was a decrease in feed intake. Stocking density allowances were seen excessively in pigs which have been shown to be necessary for maximum performance (Edwards et al, 1988).…”
Section: Effect Of Stocking Density On Growth Performancementioning
confidence: 99%